Canonical and noncanonical autophagy: involvement in Parkinson’s disease - Sakurai, Maria; Kuwahara, Tomoki (Frontiers in Cell and Developmental Biology, 2025)
Autophagy is the major degradation process in cells and is involved in a variety of physiological and pathological functions. While macroautophagy, which employs a series of molecular cascades to form ATG8-coated double membrane autophagosomes for degradation, remains the well-known type of canonical autophagy, microautophagy and chaperon-mediated autophagy have also been characterized. On the other hand, recent studies have focused on the functions of autophagy proteins beyond intracellular degradation, including noncanonical autophagy, also known as the conjugation of ATG8 to single membranes (CASM), and autophagy-related extracellular secretion. In particular, CASM is unique in that it does not require autophagy upstream mechanisms, while the ATG8 conjugation system is involved in a manner different from canonical autophagy. There have been many reports on the involvement of these autophagy-related mechanisms in neurodegenerative diseases, with Parkinson’s disease (PD) receiving particular attention because of the important roles of several causative and risk genes, including LRRK2. In this review, we will summarize and discuss the contributions of canonical and noncanonical autophagy to cellular functions, with a special focus on the pathogenesis of PD.